The place of the law in the religion of ancient Israel - Weinfeld, Moshe. (Vetus Testamentum, Supplements, 2004)
Over a hundred years ago, Wellhausen's revolutionary aim in his \'Prolegomena\' was to prove that the Priestly legal sections of the Pentateuch reflect postexilic Judaism and must be considered a deviation from the prophetic religion which preceded it. The present study points out the biased assumptions underlying Wellhausen's theory and the fallacies in this thesis. A strong case is made for the antiquity of the Priestly Code and its antedating the Book of Deuteronomy in light of many parallels between the Priestly Law and ritual texts from the Ancient Near East, and an examination of the mythic outlook in P which distinguishes it from both Deuteronomy and Second Isaiah.